5-Year results of robotic female AUS implantation: our single-center series of 42 patients - Alexandre Dubois; Claire Richard; Camille Haudebert; Juan Penafiel; Caroline Voiry; Magali Jezequel; Emmanuelle Samson; Lucas Freton; Andrea Manunta; Juliette Hascoet; Benoit Peyronnet (Therapeutic Advances in Urology)
Introduction: In recent years, several preliminary reports have suggested that the robot-assisted approach may decrease the surgical morbidity of artificial urinary sphincter (AUS) implantation in female patients with stress urinary incontinence (SUI). However, for now, only short-term outcomes have been reported. The present study aimed to report the 5-year outcomes of robot-assisted AUS implantation in female patients. Patients and methods: All female patients who underwent a robot-assisted AUS implantation between January 2014 and September 2019 at a single academic center were included in a retrospective study. All robot-assisted female AUS implantations performed after September 2019 were excluded to ensure a 5-year minimum follow-up duration. The indication for AUS implantation was SUI due to intrinsic sphincter deficiency. The primary endpoint was the explantation-free survival and revision-free survival. Results: Forty-two patients were included. The median age was 66 years (28–84), and 83.8% of the patients had a history of previous anti-incontinence procedure. After a median follow-up of 64 months (16–110), 8 patients were lost to follow-up before the 5-year time point. The 5-year estimated revision-free survival was 89.2 and the 5-year estimated explantation-free survival was 88%. Five AUS explantations were needed (11.9%), and six revisions were required (14.3%). The median time to explantation was 14 months. Four explantations (80%) occurred within the first 18 months, and all of them within the first 27 months. Thirty patients (71.42%) had a complete or improved continence with a complete continence rate of 59.52% and an improved continence rate of 11.9%. There were 10 intraoperative complications (23.8%): 5 bladder injuries and 5 vaginal injuries. Thirteen patients had postoperative complications (30.9%), but only two were Clavien grade ⩾3. Conclusion: The 5-year outcomes of robot-assisted AUS implantation seem to confirm the promising short-term outcomes that have been reported so far, although revision rates increased with time, which warrants further investigation.